Advancing Automotive Design Through Virtual Prototyping and Finite Element Analysis - Nishant Varshney (International Journal of Machine Systems and Manufacturing Technology, 2023)
Finite element analysis (FEA) and virtual prototyping are being incorporated, which is transforming the automotive sector. The design process is being revolutionized by emerging technologies, as this essay discusses, leading to automobiles that are more innovative safe, and efficient. With the help of virtual prototyping, engineers may construct, evolve, and optimize vehicle designs in an electronic environment, saving a lot of time and resources. This strategy is further enhanced using finite element analysis (FEA), which simulates structural behavior and stresses and enables engineers to improve safety, the choice of materials, and overall vehicle performance. The study demonstrates the complementary link between FEA and virtual prototyping, highlighting their combined influence on multidisciplinary teamwork, iterative design, and case-specific solutions. Real-world examples make it obvious how these technologies are altering the automotive industry's landscape by paving the way for a future filled with rapid development and cutting-edge designs.
Keywords: Design; FEA; Prototyping; Vehicle; manufacturing